Communication in smart cities between technology and role, Algeria as a model - بلاغماس سميرة; بومنجل فوزي (International Journal of Social Communication, 2023)
This research paper aims to highlight the important and main role of communication in smart cities through the advanced use of various technologies and communication technology and its role in achieving the goals of smart cities such as smart life for community members and solving complex social and technical problems. And integrating them into their cities in order to facilitate life and achieve the well-being of society. The development of the communication infrastructure in Algerian cities is an important mechanism for the embodiment of smart cities in their various dimensions.